HATCHERY PRODUCTION OF MARINE FISH WITH SPECIAL REFERENCE TO THE REPLACEMENT OF LIVE FOODS WITH MICROENCAPSULATED DIETS IN THE REARING OF THE LARVAE OF SEABASS, LATES CALCARIFER (BLOCH) - JUAN WALFORD (2020)
Ph.D